(untitled) (Research, Society and Development, 2022)
This work is a scientometric analysis of articles published in journals related to the subject “Dipteryx alata, Baru and Brazilian savanna” in its main area of occurrence, the Brazilian savanna biome. The proposal was to draw a scientometric profile related to the aforementioned topic, which is a key species with enormous potential for socio-environmental development, presenting the panorama of the state of knowledge and the main areas of research until the year 2021. A total of 205 articles that had baru as the focus of the study were found, having been published in 114 journals between 1988 and 2021. The area of biotechnology had the greatest representation, followed by ecology. In the area of biotechnology, research had different approaches, such as the nutritional part of the development of new products for the industry, highlighting the importance and plasticity for the use of the species, as a potential product for socio-environmental development, and for some communities, mainly those formed by small family units, it is an important element in complementing the source of income. Another important point of the species is its potential use for the recovery of degraded areas, due to its morphophysiological characteristics, which, in addition to helping in sustainable production and productivity, have a broad, complex and highly important ecological relationship to the Brazilian savanna ecosystem.